Reproductive features of the invasive crab Libinia dubia H. Milne Edwards, 1834 from the Central Mediterranean Sea - CHAFFAI, AMANI; RJIBA BAHRI, WAFA; GHANEM, RAOUIA; BEN SOUISSI, JAMILA (Mediterranean Marine Science, 2023)
Reproduction is a key feature in the dynamics and establishment of non-indigenous species in new areas. Thus, reproductive biology studies are particularly important for predicting whether alien species can become invasive and to pinpoint the most effective time to implement management options and mitigation actions. Here, we report the reproductive aspects of the invasive crab Libinia dubia from the central Mediterranean Sea. The population was sampled monthly for two years (January 2015 to December 2016) on the southern Tunisian coasts (Gulf of Gabès). A total of 4469 specimens were examined, of which 50.88% were males and 49.12% were females (Confidence Interval, CI = 0.015). The overall sex ratio was slightly male-biased (1: 0.97). The first gonadal sexual maturity was earlier in females than in males. Fecundity increased with crab size and weight. Libinia dubia has a single annual spawning season (March to July) in the study area. Species reproductive activity was greatest in spring, with a peak in May, while the sexual rest phase occurred during October and November in females and from September to November in males. Reproduction is one of the most influential factors in the ability of invasive species to successfully thrive and establish a population in a new environment. Our results provide important biological inputs for improving the understanding of L. dubia reproductive performance and support recommendations for research relevant to the prediction of future L. dubia invasions.